2019
DOI: 10.1029/2018jd029971
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Sunda Shelf on the Climate of the Maritime Continent

Abstract: Drastic paleogeography changes in the Indonesian archipelago over the Plio‐Pleistocene, either in response to sea level oscillations or vertical land motion, enabled the periodic emergence of the Sunda shelf. When emerged, this wide continental platform in the heart of the Maritime Continent may have modified regional and global climate systems. We investigate the effect of the exposure of the Sunda shelf on climate dynamics using a set of numerical simulations with (i) atmosphere‐land surface and (ii) fully c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 59 publications
5
14
0
Order By: Relevance
“…region (up to +5 mm.d −1 during the humid season). This bias has been described earlier with LMDZ pre-industrial simulations run either in atmospheric-only or fully-coupled mode (Toh et al, 2018;Sarr et al, 2019) and it was shown that LMDZ systematically overestimates rainfall over both land and sea surfaces of the Maritime Continent, together with western Indian Ocean and Bengal Bay. Given the complexity of the Indonesian region, with a myriad of islands that the model spatial resolution cannot capture, it is no surprise that rainfall are misrepresented in this model (Qian, 2008).…”
Section: °Csupporting
confidence: 74%
“…region (up to +5 mm.d −1 during the humid season). This bias has been described earlier with LMDZ pre-industrial simulations run either in atmospheric-only or fully-coupled mode (Toh et al, 2018;Sarr et al, 2019) and it was shown that LMDZ systematically overestimates rainfall over both land and sea surfaces of the Maritime Continent, together with western Indian Ocean and Bengal Bay. Given the complexity of the Indonesian region, with a myriad of islands that the model spatial resolution cannot capture, it is no surprise that rainfall are misrepresented in this model (Qian, 2008).…”
Section: °Csupporting
confidence: 74%
“…Although at the first order, the seasonal cycle of precipitation is correctly represented over the "Maritime Continent", IPSL-CM5A2 depicts a strong humid bias over the region (up to +5 mm d −1 during the humid season). This bias has been described earlier with LMDZ preindustrial simulations run either in atmospheric-only or fully coupled mode (Toh et al, 2018;Sarr et al, 2019) and it was shown that LMDZ systematically overestimates rainfall over both land and sea surfaces of the Maritime Continent, to- gether with western Indian Ocean and Bay of Bengal. Given the complexity of the Indonesian region, with a myriad of islands that the model spatial resolution cannot capture, it is no surprise that rainfall is misrepresented in this model (Qian, 2008).…”
Section: Tropical Precipitationsupporting
confidence: 73%
“…Jet position and AMOC have been improved, together with the sea-ice cover. IPSL-CM5A2 also benefits from higher parallelization (namely MPI-OpenMP in the atmosphere), which improves the model scalability and allows the model to reach ∼ 100 yr d −1 simulated on the JOLIOT-CURIE French supercomputer (Sarr et al, 2019;Sepulchre et al, 2019). We nonetheless first provide a validation of the model on modern climatic conditions for the Asian monsoon regions.…”
Section: Model Description and Validationmentioning
confidence: 99%